The Effectiveness of Brief Therapy in Promoting Siblings Relationship Quality and Reducing Behavioral Problems among Abused and Neglected Teenagers - Alsarhan, Qassim; M. M. Ghaith , Souad (Jordan Journal of Social Sciences, 2022)
The study aimed to examine the effectiveness of a program based on solution-centered brief therapy in enhancing the quality of the relationship between siblings and reducing behavioral problems among a sample of adolescents subjected to parental abuse and neglect. 14 teenage students participated in the study, who got the lowest scores on the scale of the quality of the relationship between siblings, and the highest scores on the behavioral problems scale. The participants were distributed equally at random into two equal groups. A counseling program was developed, and two scales were developed to measure the quality of the relationship between siblingsand behavioral problems. The program was applied over (11) sessions, for a period of (60) minutes per session. The results indicated that there were statistically significant differences between the scores of the experimental group and the control group, on all dimensions of the scale of the relationship between siblings, and the behavioral problems scale in part. This indicates the continued effectiveness of the program in enhancing the quality of the relationship between siblings, reducing behavioral problems, and maintaining the stability of this effect two weeks after its termination. The study recommended directing workers in the field of psychological and educational counseling to develop appropriate plans for adolescents who suffer from behavioral problems and weak relations between siblings.